Expression and function of estrogen receptors and estrogen-related receptors in the brain and their association with Alzheimer’s disease - Sato, Kaoru; Takayama, Ken-ichi; Inoue, Satoshi (Frontiers in Endocrinology, 2023)
While estrogens are well known for their pivotal role in the female reproductive system, they also play a crucial function in regulating physiological processes associated with learning and memory in the brain. Moreover, they have neuroprotective effects in the pathogenesis of Alzheimer's disease (AD). Importantly, AD has a higher incidence in older and postmenopausal women than in men, and estrogen treatment might reduce the risk of AD in these women. In general, estrogens bind to and activate estrogen receptors (ERs)-mediated transcriptional machineries, and also stimulate signal transduction through membrane ERs (mERs). Estrogen-related receptors (ERRs), which share homologous sequences with ERs but lack estrogen-binding capabilities, are widely and highly expressed in the human brain and have also been implicated in AD pathogenesis. In this review, we primarily provide a summary of ER and ERR expression patterns in the human brain. In addition, we summarize recent studies on their role in learning and memory. We then review and discuss research that has elucidated the functions and importance of ERs and ERRs in AD pathogenesis, including their role in Aβ clearance and the reduction of phosphorylated tau levels. Elucidation of the mechanisms underlying ER-and ERR-mediated transcriptional machineries and their functions in healthy and diseased brains would provide new perspectives for the diagnosis and treatment of AD. Furthermore, exploring the potential role of estrogens and their receptors, ERs, in AD will facilitate a better understanding of the sex differences observed in AD, and lead to novel sex-specific therapeutic approaches.